Microwave-Assisted Synthesis of Some Quinoxaline-Incorporated Schiff Bases and Their Biological Evaluation - L. Achutha; R. Parameshwar; B. Madhava Reddy; V. Harinadha Babu (Journal of Chemistry)
Quinoxaline-incorporated Schiff bases (4a–j) were synthesized by the condensation of 2-[(3-methylquinoxalin-2-yl)oxy]acetohydrazide (3) with indole-3-carbaldehyde, furfuraldehyde, 5-(4-nitrophenyl)-2-furfuraldehyde, and substituted benzaldehydes under conventional and microwave irradiation methods. The microwave method was found to be remarkably successful with higher yields, less reaction time, and environmentally friendly compared to conventional heating method. The chemical structures of the synthesized compounds have been confirmed by analytical and spectral data. All the compounds have been evaluated for antitubercular and anti-inflammatory activities.